New records of Ephemeroptera (Insecta) from Roraima State, Northern Brazil - Gama Neto, Jaime de Liege; Passos, Mahedy Araujo Bastos; Cruz, Jenisson Araujo; Souza, Nazareno Trajano de (EntomoBrasilis, 2018)
Abstract. The aim of this work is to present new records and distributional notes of Ephemeroptera species on Roraima states. Farrodes maculatus Domínguez, Molineri & Peters, 1996, Hermanellopsis incertans (Spieth, 1943) and Thraulodes marreroi Chacón, Segnini & Domínguez, 1999 are recorded for the first time in Brazil. Family Coryphoridae, Callibaetis cruentus Cruz, Salles & Hamada, 2014, Callibaetis gelidus Cruz, Salles & Hamada, 2014, Campylocia demoulini Gonçalves & Salles, 2017, Coryphorus aquilus Peters, 1981, Fittkaulus cururuensis Savage, 1986, Fittkaulus maculatus Savage & Peters, 1978, Miroculis fittkaui Savage & Peters, 1983, and Simothraulopsis sabalo Kluge, 2007 are recorded for the first time in Roraima. The number of known species of Ephemeroptera in Roraima, after our study, has increased from 64 to 75. Novos registros de Ephemeroptera (Insecta) do Estado de Roraima, norte do Brasil Resumo. O objetivo deste trabalho é apresentar novos registros de espécies e notas sobre a distribuição geográfica de Ephemeroptera no Estado de Roraima. As espécies Farrodes maculatus Domínguez, Molineri & Peters, 1996, Hermanellopsis incertans (Spieth, 1943) e Thraulodes marreroi Chacón, Segnini & Domínguez, 1999 são registradas pela primeira vez no Brasil. A família Coryphoridae e as espécies Callibaetis cruentus Cruz, Salles & Hamada, 2014, Callibaetis gelidus Cruz, Salles & Hamada, 2014, Campylocia demoulini Gonçalves & Salles, 2017, Coryphorus aquilus Peters, 1981, Fittkaulus cururuensis Savage, 1986, Fittkaulus maculatus Savage & Peters, 1978, Miroculis fittkaui Savage & Peters, 1983 and Simothraulopsis sabalo Kluge, 2007 são registradas pela primeira vez no estado de Roraima. O número de espécies de Ephemeroptera com registros de ocorrência em Roraima é elevado de 64 a 75.